Quantum mechanical study of electronic properties of zigzag nanotubes (9,0) (SWCNTs) - AL-Ani, Huda N. (Iraqi Journal of Physics, 2019)
Quantum calculations on the most stable structure were carried out for calculating the electronic properties, energies and the charge density at the Carbon and Hydrogen atoms by Semi-empirical method (PM3) of zigzag carbon nano tube CNT (9,0) (SWCNTs), at the equilibrium geometry depending on the pictures of Zigzag CNT(9,0) which was found to has D3d symmetry point group by applying for (Gaussian 2003) program. In this work the results include calculation the relation for axial bonds length, which are the vertical C-C bonds (annular bonds) in the rings and bonds length which are in the outer ring that called the circumferential bonds. Also include a different kind of vibration modes like breathing, puckering, and deformation bending. They allow a comparative view of the charge density at the carbon atom too. The aromaticity is graded according to the space distribution of the atoms in zigzag nano tube (9,0), the nature of their molecular orbitals depend on, their symmetry, and chirality. Many studies were done measurements to characterize nanotube mechanical properties for successful applications in nanotechnology.